PENINGKATAN KETUNTASAN BELAJAR SISWA DENGAN PENERAPAN MODEL ROLE PLAYING PADA MATA PELAJARAN MERENCANAKAN DAN MELAKUKAN PERTEMUAN - Lia Wulandarilia Wulandari, (Pendidikan Ekonomi, 2010)
This study is intended to find out how role playing as a learning model is implemented to increase the students learning mastery. The subjects were the ten graders of APK 1 SMK Negeri 10 Surabaya consisting of 40 students. The data collection method used in this research was descriptive qualitative. The method classroom action reseach method. The findings show that the students were actively engaged in the learning process and the students learning mastery increased in each cycles, namely, 50%, 75%, 87,5% dan 95% respectively.